​​Integrating machine learning and spatial transcriptomics uncovers shared immunomodulatory deubiquitinases in MAFLD and HCC - Yu-xi Han; Hongze Li; Wendi Xia; Junyi Ma; Jiaqi Zhang; Yiling Li (Human Genetics, 2026)

Multiscale solvation-electronic regulation strategy toward stable Zn anode - Jiaqi Li; Yushan Ma; Yicheng Wang; Shaoyu Zhang; Jiaming Li; Nan Li; Junyi Han; Hedong Gu; Zhanhong Yang; Xiaolei Wang (Chemical Engineering Journal, 2026)

Design and Evaluation of Sequential Near-Bottom Mobile Organism Sampling Equipment Intended for Deep-Sea Mining Plume-Affected Zones - Kaichuang Wang; Haiyang You; Xinghui Tan; Jiale Wu; Bo Han; Junyi Yang; Congchi Huang; Jiawang Chen; Jin Guo (Journal of Marine Science and Engineering, 2026)
Deep-sea mining generates plumes containing heavy metals harmful to marine ecosystems. Assessing their impact on benthic organisms is essential. Traditional monitoring methods commonly employ acoustic, optical, and electrical approaches to investigate collective behaviors of organisms, while direct acquisition and in situ preservation of biological specimens during deployment remain challenging. To address this limitation, a novel sequential near-bottom mobile organisms sampling equipment equipped with multiple chambers was developed. Sequential sampling of near-bottom mobile organisms was conducted to obtain samples at different time points for individual-level biological assessment. This study investigates the alcohol diffusion dynamics at various injection volumes. The results show that during injection, alcohol is concentrated in the upper section of the chamber. When 5.0 L of alcohol is introduced, the alcohol mass fraction within the sampling container rapidly reaches and stabilizes at 87%. The sampling equipment’s performance was evaluated through dock experiments and deep-sea trials at a depth of 1571 m in the South China Sea. Field tests successfully captured five jellyfish, with alcohol mass fractions of 85%, 87%, and 87% achieved in the respective chambers. These results demonstrate the feasibility of the equipment for sequential biological sampling and in situ preservation in deep-sea environments.

A behavior-calibrated framework for prioritizing pesticide co-residue burdens in routine monitoring: Method development and a district-level pilot study in Shanghai - Bo Ding; Xiaoxing Lu; Hua Deng; Yuting Zhang; Junyi Shen; Ruobing Han; Jixing Yang (Food and Humanity, 2026)

Genome-characterized Lacticaseibacillus rhamnosus Hao9 alleviates DSS–induced chronic low-grade inflammation and modulates the gut microbiota - Minxin Yang; Jinyan Yu; Shengliang Wang; Xianyan Liao; Mei Han; Junyi Huang (Food Bioscience, 2026)

Trade-off-free intrinsically stretchable electroluminescent films enabled by a thermally activated delayed fluorescence plasticizer - Wenzhong Bian; Xinxin Ban; Junyi Chen; Mengting Li; Caixia Yang; Hongyu Zhuang; Shuang Chen; Jiangqi Jiang; Wenli Shi; Hai Zhou; Youqiang Qian; Zhaoxiang Han; et al. (Chemical Engineering Journal, 2026)

Time-Resolved Oxidative Stress and Apoptosis in Murine Retina under Acute Hypobaric Hypoxia with Parallel Activation of the LIF–JAK–STAT3 Axis - Hao Wang; Qiang Ye; Songjian Huang; Keke Ge; Cong Han; Huan Xi; Junyi Qiao; Jingrong Feng; Peirun Wu; Yuhan Bao; Yi Yang; Wenfang Zhang (Molecular Neurobiology, 2026)

Nutritional modulation of pork quality: SID lysine levels alter meat quality, and flavor-associated metabolites in growing-finishing pigs - Junyi Pan; Saipeng Han; Qingyao Wu; Jiashun Chen; Ruilin Huang; Qiuping Guo (Food Chemistry, 2025)

The Age and Growth of One Population of Diaphus watasei (Jordan & Starks, 1904) in the South China Sea - Kui Zhang; Han Tian; Yan’e Jiang; Shannan Xu; Jiangfeng Zhu; Junyi Zhang; Jun Zhang; Zuozhi Chen (Fishes, 2025)
We estimated, for the first time, the age of Diaphus watasei (Jordan & Starks, 1904) in the South China Sea (SCS) based on otolith microstructure. According to one-way ANOVA, differences were not observed between the sexes with regard to standard length, body mass, or age. Based on 137 specimens, the sex ratio and relationship between standard length and body mass was 1.32:1 (male/female) and W = 0.0000433L2.78 (r2 = 0.923), respectively. The von Bertalanffy model was fitted as Lt = 171.38 [1 − exp(−0.00206(t − 3.82))], r2 = 0.645 (n = 92), which indicated a maximum growth rate of 0.356 mm/day. The speculated birth date of the 92 specimens of D. watasei occurred across almost all months of the year.

Preventive and Therapeutic Potential of Streptococcus cristatus CA119 in Experimental Periodontitis in Rats - Dongyu Zhao; Ming-Han Li; Tianxu Pan; Jialin Guo; Junyi Li; Chunwei Shi; Nan Wang; Haibin Huang; Chunfeng Wang; Guilian Yang (Probiotics and Antimicrobial Proteins, 2025)

Experimental and theoretical research of erbium engineering in carbon-based composite membrane for self-cleaning and oil-water separation - Zexin Li; Junyi Zhang; Mingyang Chu; Zhilun Li; Yuxi Chen; Qiang Han; Qi Zhang; Jihui Lang; Yan Yan (Journal of Environmental Management, 2025)

A wild-allele GsPP2C-51-a1 enhances tolerance to drought stress in soybean and Arabidopsis - Cheng Liu; Xianlian Chen; Wei Han; Xiaoshuai Hao; Liang Qin; Wei Luo; Lizhi Zhao; Ning Li; Lei Sun; Jiaoping Zhang; Guangnan Xing; Jianbo He; et al. (Theoretical and Applied Genetics, 2025)

Hydrogel ionic diode with ultra-high rectification ratio for ionic circuit - Yanqing Wei; Yize Zhao; Qun Ding; Junyi Zhao; Yibing Yang; Yang Liu; Jidong Dong; Dawei Zhang; Shuaiyuan Han; Pengfei Huo (Chemical Engineering Journal, 2024)

Continuous cropping disorders of eggplants (Solanum melongena L.) and tomatoes (Solanum lycopersicum L.) in suburban agriculture: Microbial structure and assembly processes - Zufei Xiao; Changyi Lu; Zhiyong Wu; Xinyuan Li; Kai Ding; Zhe Zhu; Ruixia Han; Junyi Zhao; Tida Ge; Gang Li; Yong-Guan Zhu (Science of The Total Environment, 2024)

High frequency measurement of carbon emissions based on power big data: A case study of Chinese Qinghai province - Junyi Shi; Huaqing Tang; Qunxing Zhou; Liangyu Han; Ri Hao (Science of The Total Environment, 2023)

Detection of Multi-dimensional Driving Forces of Public Environmental Concern in China: Based on Spatial Heterogeneity Perspectives - Yun Tong; Li Pang; Minghui Sun; Junyi Han (Chinese Geographical Science, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Status and trends of enzyme cocktails for efficient and ecological production in the pulp and paper industry - Manli Yang; Junyi Li; Shuai Wang; Fengguang Zhao; Chenyang Zhang; Chunhui Zhang; Shuangyan Han (Journal of Cleaner Production, 2023)

Reassessing the age of the Early Pleistocene Longgupo fauna, southern China: An updated magnetostratigraphic perspective - LU SUN; CHENGLONG DENG; CAICAI LIU; JUNYI GE; SHIXIA YANG; SHUAI ZHANG; FEI HAN; JEAN‐JACQUES BAHAIN; MICHEL RASSE; ÉRIC BOËDA; YAMEI HOU; GUANGBIAO WEI; et al. (Journal of Quaternary Science, 2023)
As the northernmost locality yielding one of the most representative Early Pleistocene Gigantopithecus – Sinomastodon faunas in southern China, the Longgupo site has preserved valuable geological archives that have significantly improved our understanding of Pleistocene biostratigraphy and biogeography. A convincing chronological framework of this locality is therefore important to elaborate on the evolution of Quaternary faunas as well as paleoenvironment. To reconcile the existing geochronological results with new advances in geochronology and biochronology, we present here a revised magnetostratigraphic age model based on detailed rock magnetic and paleomagnetic data and strengthened by biochronology as well as recently published electron spin resonance and uranium series (ESR/U‐series) age data. Two geomagnetic polarities were identified from the Longgupo sequence: the upper one is thin and normal, corresponding to the Olduvai normal subchron; and the lower one is distinctly thick and reversed, corresponding to the pre‐Olduvai Matuyama Chron. The age of the Longgupo fauna constrained by this refined magnetochronological framework is therefore estimated to be about 2.5–2.0 Ma, consistent with the newly published ESR/U‐series age of 2.5–2.2 Ma.

Application of earthworm and silicon can alleviate antibiotic resistance in soil-Chinese cabbage system with ARGs contamination - Zufei Xiao; Ruixia Han; Jianqiang Su; Zhe Zhu; Yi Zhao; Qinglin Chen; Junyi Zhao; Gang Li; Yong-Guan Zhu (Environmental Pollution, 2023)

Association between ambient air pollution exposure during pregnancy and gestational diabetes mellitus: a meta-analysis of cohort studies - Xinyu Zhou; Changlian Li; Han Cheng; Junyi Xie; Feng Li; Lishan Wang; Rui Ding (Environmental Science and Pollution Research, 2022)

Genetic variants in choline metabolism pathway are associated with the risk of bladder cancer in the Chinese population - Zhichao Han; Jingjing Gu; Junyi Xin; Hanting Liu; Yanling Wu; Mulong Du; Haiyan Chu; Yadong Liu; Zhengdong Zhang (Archives of Toxicology, 2022)

Tidal currents in the coastal waters east of Hainan Island in winter - Min Li; Lingling Xie; Xiaolong Zong; Junyi Li; Mingming Li; Tong Yan; Ronglei Han (Journal of Oceanology and Limnology, 2022)

Enhanced antioxidant capacity and upregulated transporter genes contribute to the UV-B-induced increase in blinin in Conyza blinii - Junyi Zhan; Qin Yang; Zhiyi Lin; Tianrun Zheng; Maojia Wang; Wenjun Sun; Tongliang Bu; Zizhong Tang; Chenglei Li; Xueyi Han; Haixia Zhao; Qi Wu; et al. (Environmental Science and Pollution Research, 2021)

Interaction between serine carboxypeptidase-like protein TtGS5 and Annexin D1 in developing seeds of Triticum timopheevi - Peihong Jiang; JianSheng Gao; Junyi Mu; Luning Duan; Yunsong Gu; Shichen Han; Lin Chen; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2020)

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

Genome-wide identification of internal reference genes for normalization of gene expression values during endosperm development in wheat - Junyi Mu; Lin Chen; Yunsong Gu; Luning Duan; Shichen Han; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2019)

Simultaneous addition of zero-valent iron and activated carbon on enhanced mesophilic anaerobic digestion of waste-activated sludge - Tongyu Wang; Yujie Qin; Yan Cao; Bin Han; Junyi Ren (Environmental Science and Pollution Research, 2017)

Identification and characterization of Orf virus 050 protein proteolysis - Han Wang; Junyi Jiang; Rui Ding; Xiaoping Wang; Meiying Liao; Jing Shao; Xiaohong Luo; Shuhong Luo; Chaohui Duan (Virus Genes, 2017)

Different responses of soybean cyst nematode resistance between two RIL populations derived from Peking × 7605 under two ecological sites - YONGCHUN LI; NA GUO; JINMING ZHAO; BIN ZHOU; RAN XU; HUI DING; WEIGUO ZHAO; JUNYI GAI; HAN XING (Journal of Genetics, 2016)

Association of POLK Polymorphisms with Platinum-Based Chemotherapy Response and Severe Toxicity in Non-small Cell Lung Cancer Patients - Minhua Shao; Bo Jin; Yanjie Niu; Junyi Ye; Daru Lu; Baohui Han (Cell Biochemistry and Biophysics, 2014)

Computational identification of novel microRNAs and targets in Glycine max - Na Guo; Wenwu Ye; Qiang Yan; Jing Huang; Yuren Wu; Danyu Shen; Junyi Gai; Daolong Dou; Han Xing (Molecular Biology Reports, 2014)

Decreased expression of miR-126 correlates with metastatic recurrence of hepatocellular carcinoma - Hongyuan Chen; Ruizheng Miao; Junwei Fan; Zhongbo Han; Junyi Wu; Guoqiang Qiu; Huamei Tang; Zhihai Peng (Clinical & Experimental Metastasis, 2013)

A comparative proteomics analysis of soybean leaves under biotic and abiotic treatments - Jinming Zhao; Yumei Zhang; Xiaochun Bian; Jun Lei; Jutao Sun; Na Guo; Junyi Gai; Han Xing (Molecular Biology Reports, 2013)